XueBiJing injection reduced mortality in sepsis patients with diabetes - Liu, Yan; Dai, Hengheng; Li, Yixuan; Yang, Tianyi; Zhang, Dandan; Hu, Chaoyue; Liu, Si; Feng, Zhiqiao; Zhang, Chi; Yang, Xiaohui (Frontiers in Pharmacology, 2025)
IntroductionSepsis patients with diabetes are at a high clinical risk. It is well reported that XueBiJing injection has good clinical benefit in sepsis individuals. However, there is no relevant report about the efficacy and safety of XBJ in sepsis patients with comorbid diabetes.MethodsData of two large randomized controlled clinical trials (XBJ-SAP (ChiCTR-TRC-13003534) and EXIT-SEP (NCT0323874)) were combined, and post hoc analyses were performed. Sepsis patients with diabetes were further divided into the XBJ-treated group and placebo group based on inclusion and exclusion criteria. The primary (28-day mortality) and secondary outcomes (mortality in the ICU and in the post-randomization hospital, acute physiology, and chronic health evaluation II (APACHE II) score and sequential organ failure assessment (SOFA) score) were compared between the XBJ treatment and placebo groups in sepsis patients with the diabetes status at baseline. Moreover, the occurrence of adverse events (AEs) was also assessed.ResultsAt the study baseline, a total of 378 sepsis patients (227 men [60.0%] and 151 women [40.0%]; mean [SD] age, 60.3 [11.1] years) were considered to have diabetes, of which 177 received XBJ and 201 received placebo administration. Among these sepsis patients with diabetes, the mortality at 28 days was significantly lower in the XBJ group than in the placebo group (29 of 173 patients [16.8%] vs. 56 of 198 patients [28.3%], P = 0.01), and the absolute risk difference was 11.5% (95% CI, 3.1%–19.9%). Furthermore, there was no difference in the overall incidence of adverse events (AEs) when XBJ was used (24.4% [42 of 172 patients] vs. 27.7% [54 of 195 patients].DiscussionThe present study underscores the pivotal role of XBJ in modulating the immune response among sepsis patients suffering from diabetes mellitus, exploring the positive effects of XBJ on sepsis patients with diabetes mellitus. The efficacy and safety of XBJ compared with those of the placebo were consistent with the overall trial findings, demonstrating that XBJ is efficacious in sepsis patients with diabetes and suggesting that there is no need for special safety precautions.Trial Registration IdentifierChiCTR-TRC-13003534 and NCT0323874.